Persistent lymphopenia after kidney transplantation: increased mortality and decreased homeostatic mechanisms - Liang, Yun; Smith, Byron; Park, Walter; Li, Zhihao; Abdelrheem, Ahmed; Kesik, Esma; Mejia, Mateo Velasquez; Pavelko, Kevin; Jessen, Erik; Jarmi, Tambi; Mour, Girish K.; Nair, Sumi S.; et al. (Frontiers in Immunology, 2025)
IntroductionKidney transplant (KTx) recipients commonly develop transient lymphopenia due to treatment with alemtuzumab, rabbit anti-thymocyte globulin (rATG) or other conditions. However, persistent lymphopenia lasting for years has not been studied in detail. The goal of this study was to determine the prevalence of persistent lymphopenia, evaluate its association with mortality and investigate possible mechanisms by which it occurs. MethodsWe retrospectively studied peripheral blood lymphocyte and leukocyte counts in 7307 adult, solitary renal transplant recipients transplanted between 1/2006 to 12/2020. ResultsWhile leukocyte counts generally remained within the normal range, lymphocyte counts 3 years after KTx were below normal in 31% (compared to 14% pretransplant and 54% at 1 year). Increasing severity of lymphopenia at 3 years was associated with increasing risk of mortality. The major risk factors for lymphopenia at 3 years were: receiving alemtuzumab or rATG for induction or the treatment of rejection, increasing recipient age, pretransplant dialysis, a low lymphocyte count pretransplant, and having a prior kidney transplant. Mass cytometry immunophenotyping at 3 years showed that B cells, NK cells and all T cell subsets (CD4, CD8, naïve, memory, etc.) decreased with decreasing lymphocyte counts. This included fewer recent thymic emigrants, naïve T cells, and stem-cell like memory T cells (TSCM), suggesting an impaired homeostasis of peripheral T cells. PD-1 expression was increased with decreasing lymphocyte counts in T and B cells and in most T cell subsets including CD4 TSCM, CD4 and CD8 naïve cells, and CD4 recent thymic emigrants. DiscussionWe conclude that persistent lymphopenia might be partially due to impaired homeostatic mechanisms in T, B and NK cells and might be a simple, useful biomarker for individualizing patient management.